Sensory Impairment and recovery After Stroke - Connell, Louise Anne (2007)
Sensory impairment is common after stroke though problems with the assessment of sensation have hindered research into sensation and its recovery. The revised Nottingham Sensory Assessment [NSA] (Lincoln et al, 1998) is a standardised assessment but there have been difficulties interpreting results, as it is not possible to calculate total scores.